Negative Entrenchment Effect of Business Group Conglomerates on Selling and Purchasing Related Party Transactions - Dayinta Ayuningtyas; Vera Diyanty (Journal of Economics, Business, and Accountancy Ventura, 2016)
This study aims to explain the negative entrenchment effect arised from selling and purchasing related party transactions on business group conglomerates. This study is using 322 firm-year data of firms listed at Indonesia Stock Exchange in 2012-2013 period.This research provides evidence that the ownership by business conglomerates strengthened the negative entrenchment effect in both total of selling-purchasing related party transactions and selling-purchasing related party transactions which come from operating activities. Thus, from the result, it can be presumed that there might be a possibility of agency conflict arised from selling-purchasing related party transactions when a firm is part of business conglomerates.